2018
DOI: 10.3390/w10040360
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size Distribution of Bedload Transport in a Glaciated Catchment (Baranowski Glacier, King George Island, Western Antarctica)

Abstract: Abstract:The relationships among grain size distribution (GSD), water discharge, and GSD parameters are investigated to identify regularities in the evolution of two gravel-bed proglacial troughs: Fosa Creek and Siodło Creek. In addition, the potential application of certain parameters obtained from the GSD analysis for the assessment of the formation stage of both creeks is comprehensively discussed. To achieve these goals, River Bedload Traps (RBTs) were used to collect the bedload, and a sieving method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…These locations are cut by numerous and periodically active troughs. Sziło and Bialik [39] suggested that the rapid changes in the geomorphology of this part of the Baranowski Glacier forefield were due to the high energetic differentiation of the sediment particles. Furthermore, it has been shown that the differences between two creeks, Fosa and Siodło, are due to their relative stage of formation and position of the glacier terminus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These locations are cut by numerous and periodically active troughs. Sziło and Bialik [39] suggested that the rapid changes in the geomorphology of this part of the Baranowski Glacier forefield were due to the high energetic differentiation of the sediment particles. Furthermore, it has been shown that the differences between two creeks, Fosa and Siodło, are due to their relative stage of formation and position of the glacier terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Its frontal part is divided into two tongues: the northern tongue and the southern tongue. An ice cliff is present where the northern tongue terminates in close proximity to a coastal lagoon, which is separated from Staszek Cove by a narrow spit during low tides [39,43]. The southern tongue terminates approximately 240 m from the recent shoreline with a varied forefield of proglacial landforms.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the papers in the Special Issue follows, given in the order in which they appear. The grain size distribution of bedload transported within a given water discharge has been investigated for two polar catchments in Antarctica [45], aimed at determining how the grain size distribution is modified during times of peak discharge, determining the relationship between the grain size distribution and its parameters, and the amount of transported material in gravel-bed rivers, and examining whether the modification of grain size distribution during efficient bedload transport events allow for the identification of the development stage of river throughs during changing meteorological conditions. These questions were answered after a measurement campaign in two creeks with proglacial gravel-bed channels.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…The erosion and sediment transport issues have been investigated in channels and over watersheds. The channels have been either a prototype natural watercourse [45,54] or an artificial flume of a laboratory model [46,54]. As for the watersheds, the scale has changed from 1.25 km 2 subcatchments from the United Kingdom [53] to large, millions of km 2 watersheds in the Maghrib basin that extend over Morocco, Algeria, and Tunisia.…”
Section: Establishment Of the Special Issuementioning
confidence: 99%